Biological Properties and Absolute Configuration of Flavanones from Calceolaria Thyrsiflora Graham - Montoya-Kunsting, M; Mascayano-Collado, C; Vasquez-Martinez, y; Cortez-San Martin, M; Mejías-Medina, S; Cabezas-Gómez, F; Torrent-Farias, C (Frontiers Media S.A., 2020)
Flavanones (–)-(2S)-5,4’-dihydroxy-7-methoxyflavanone (1) and (–)-(2S)-5,3’,4’-trihydroxy-7-methoxyflavanone (2) were isolated from the extracts of Calceolaria thyrsiflora Graham, an endemic perennial small shrub growing in the central zone of Chile. The absolute configuration of these compounds was resolved by optical rotation experiments and in silico calculations. Three analogs (3, 4, and 5) were synthesized to do structure-activity relationships with the biological assays studied. Biological tests revealed that only flavanone 2 exhibited a moderate inhibitory activity against the methicillin-resistant strain S. aureus MRSA 97-77 (MIC value of 50 µg/ml). In addition, flavanone 2 showed a potent, selective, and competitive inhibition of 5-hLOX, which supports the traditional use of this plant as an anti-inflammatory in diseases of the respiratory tract. Also, 2 exhibited cytotoxic and selective effects against B16-F10 (8.07 ± 1.61 µM) but 4.6- and 17-fold lesser activity than etoposide and taxol. © Copyright © 2020 Valdés, González, Díaz, Vásquez-Martínez, Mascayano, Torrent, Cabezas, Mejias, Montoya, Cortez-San Martín, Muñoz, Joseph-Nathan, Osorio and Taborga.